Single Mother Parenting in Preschool Children’s Social-Emotional Development - Arlianty, Lia Shafira; Setiawan, Nissa Rahmadhini; Achdiani, Yani (Indonesian Journal of Community and Special Needs Education, 2025)
Single-parent families, particularly those led by single mothers, are becoming more common in society. These mothers often face dual responsibilities of caregiving and providing financially, which can affect the social-emotional development of their children. This study aims to examine the parenting process, type, and its impact on preschool children’s social-emotional development because early childhood is a critical period for forming emotional and social skills. Using a qualitative descriptive method, data were collected through interviews and observations involving two single mothers and their children’s teachers. The results show that democratic parenting encourages positive outcomes such as confidence, empathy, socialization, and rule-following. However, permissive elements within parenting may lead to aggression, low empathy, and difficulty following rules. Because parenting directly influences a child's development, single mothers need support and guidance. This study highlights the importance of promoting democratic parenting to help single mothers nurture preschool children's social-emotional growth in line with developmental indicators.